Pengaruh Kewirausahaan Mahasiswa terhadap Kinerja Belajar: Systematic Literature Review - Masduki Asbari (Motivaksi: Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2026)
Student entrepreneurship has become an important focus in higher education as a means of developing competencies and work readiness. This study aims to analyze the influence of student entrepreneurial activities on various aspects of learning performance, including academic achievement (GPA), cognitive abilities, communication and public speaking skills, social skills, and other performance aspects through a systematic literature review. A systematic review method was applied by analyzing 45 scientific articles from accredited national and reputable international journals published in the 2019-2025 range. The analysis results show that student entrepreneurial activities have a significant positive impact on learning performance through the mediation mechanisms of self-efficacy, creativity, and problem-solving skills. Students involved in entrepreneurial activities showed an increase in soft skills (teamwork, communication, networking) of 18-32% compared to non-entrepreneurial students. However, there is a curvilinear relationship between the intensity of entrepreneurial activities and GPA, where the optimal intensity is at 10-15 hours per week. This research provides a theoretical contribution in understanding the complex mechanisms between entrepreneurship and academic performance, as well as practical implications for the development of entrepreneurship education curricula in higher education.